Study the effect ofmagnet icfield on the properties of silver thin films prepared by dc sputtering - Abdulhussain A .Khadayeir; shimaa Rajh .Taly (Al-Qadisiyah Journal of Pure Science, 2018)
Silver thin films by Dc  sputtering method on  glass substrate for different deposition times (10,30 and 60)sechave been  prepared and deposited . The thicknesses of Ag thin films  measured by using an optical interferometer method employing He-Ne laser (632.8)nm wavelength . Thin films thicknesses  without magnetic field was (84,89 and 94)nm while with magnetic field was(127,269 and 290)nm for same times. Structure and Optical properties have been analyzed by using XRD and UV-V spectroscopy  and XRD analysis show that thin films were face centered cubic structure. Absorption and Transmittance spectra of silver thin films were recorded in the wavelength range between 300nm to1100nm . High absorption coefficient of silver thin films determined from the analysis of absorption spectra  . The electrical properties show the resistivity  inversely proportional with silver thin films  thickness.